2019
DOI: 10.1016/j.cpc.2019.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Thick-restart block Lanczos method for large-scale shell-model calculations

Abstract: We propose a thick-restart block Lanczos method, which is an extension of the thick-restart Lanczos method with the block algorithm, as an eigensolver of the large-scale shell-model calculations. This method has two advantages over the conventional Lanczos method: the precise computations of the near-degenerate eigenvalues, and the efficient computations for obtaining a large number of eigenvalues. These features are quite advantageous to compute highly excited states where the eigenvalue density is rather hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(130 citation statements)
references
References 41 publications
5
124
0
1
Order By: Relevance
“…This is achieved by partitioning the single-particle basis into core, valence, and beyond-valence states, normal ordering all operators with respect to a Slater determinant describing the closed-shell core, and extending the definition of the off-diagonal Hamiltonian (23) to include all terms that couple valence and non-valence states. The eigenvalue problem for the evolved Hamiltonian can then be solved in the valence space with widely available Shell model codes [89][90][91][92][93]. After a study of the oxygen isotopic chain revealed an increasing overbinding away from the chosen core [26], we adopted a normal-ordering scheme that uses an ensemble of Slater determinants to account for partially filled shells in open-shell nuclei [27,54]…”
Section: In-medium Similarity Renormalization Groupmentioning
confidence: 99%
“…This is achieved by partitioning the single-particle basis into core, valence, and beyond-valence states, normal ordering all operators with respect to a Slater determinant describing the closed-shell core, and extending the definition of the off-diagonal Hamiltonian (23) to include all terms that couple valence and non-valence states. The eigenvalue problem for the evolved Hamiltonian can then be solved in the valence space with widely available Shell model codes [89][90][91][92][93]. After a study of the oxygen isotopic chain revealed an increasing overbinding away from the chosen core [26], we adopted a normal-ordering scheme that uses an ensemble of Slater determinants to account for partially filled shells in open-shell nuclei [27,54]…”
Section: In-medium Similarity Renormalization Groupmentioning
confidence: 99%
“…We discuss exceptions to this below. Finally the resulting valence-space Hamiltonians are diagonalized with the NuShellX@MSU shell-model code [46] (with the exception of a few of the heaviest Ca, Sc and Ti isotopes, which were computed with the m-scheme code K-shell [47]).…”
mentioning
confidence: 99%
“…Together with Lemma 1 and the premise, we find Multiplying w H k+1 and v H k+1 to (17) and (18), respectively, yields…”
Section: Theorem 1 Letmentioning
confidence: 67%
“…However, with finite precision arithmetic, the single-vector Lanczos process would generate a small overlap to W k via round-off errors, so that even after the convergence of an eigenvector, a late convergence to the other paired eigenvector would be possible. Because this behavior is rather accidental, a block-type Lanczos algorithm has to be applied to accelerate the convergence for degenerate eigenvectors [1,2,8,18,22].…”
Section: Corollarymentioning
confidence: 99%
See 1 more Smart Citation